Finite A-groups with complementable nonmetacyclic subgroups - Baryshovets, P. P. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We study groups G, satisfying the following conditions:1)G — is a finite soluble group with nontrivial prime-power metacyclic second commutator subgroup;2)all Sylow subgroups of G are elementary Abelian.We describe the structure of these groups with complemented nonmetacyclic subgroup.